Trends and Development of Research on Flipped Classroom in Education: A Bibliometric Analysis from 2012 to 2024 - Ira Nur Amalia; Irwanto Irwanto; Kamran-ul-Haq Khan (Scientia Publica Media, 2025)
Nowadays, advancements in ICT have positively impacted education. This bibliometric study examines trends and developments in research on flipped classrooms in education from 2012 to 2024, focusing on the impact of technological advancements in supporting student-centered learning. The flipped classroom approach allows students to learn course materials independently before class sessions, where active discussions, problem-solving, and collaboration become the primary activities. Using data from Scopus, 1,580 relevant research articles were analyzed to reveal publication trends, influential contributions, and key themes. The analysis highlights the role of flipped classrooms in enhancing students’ critical thinking, independent learning, and intrinsic motivation. Findings indicate a growing research interest in this model, particularly in higher education and science disciplines, with significant growth during and after the COVID-19 pandemic, with an impressive annual growth rate of 53.34%. These publications involved contributions from 4,226 authors, with Wang Y emerging as the most prolific author. The documents were distributed across 639 different sources, with BMC Medical Education recognized as the most productive source. In terms of geographical distribution, the United States led with the highest number of publications. The University of California was identified as the institution with the largest number of publications. The most frequently used keywords in these studies included students, teaching, education, curriculum, human, learning, humans, article, medical, and male. This study provides insights into collaborative networks, influential publications, and the latest research trends, offering guidance for educators, policymakers, and researchers in planning future studies and implementing flipped classrooms effectively.